Dynamic Agency and Large‐Risk Taking. (29th December 2017) - Li, Rui
Abstract: I propose a dynamic investment model with moral hazard under which greater exposure to future uncertainties about losses could enhance incentive provisions and improve firm value. The model provides an explanation for why many financial companies and investment banks choose to improve their short‐run performance by putting themselves at greater risk of catastrophic losses in the future, as what happened prior to the 2007 financial crisis.